2023
DOI: 10.1055/s-0043-1771293
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Anabolic Androgenic Steroid-Induced Gynecomastia

Abstract: Introduction Gynecomastia is benign proliferation of male breast tissue that can be idiopathic or secondary to hormonal imbalance. Consumption of steroids plays a major role in the development of gynecomastia. The increased consumption of anabolic androgenic steroid (AAS) in youngsters to boost the physical strength and improve appearance is associated with increased prevalence of gynecomastia. True estimation of AAS-associated gynecomastia is difficult to calculate and prone to underestimation because of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Surgery is not always indicated in gynecomastia associated with AASs, as the prevalence of meticulous intraoperative hemostasis and a careful glandular excision are common to minimize recurrence and achieve low complication rates [45]. Studies conducted on the effects of AAS use and abuse on the prostate gland have shown that the chronic use of these substances can promote prostatic hyperplasia and hypertrophy [42,46,47].…”
Section: The Association Of Aass With the Circulatory System And Sexu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is not always indicated in gynecomastia associated with AASs, as the prevalence of meticulous intraoperative hemostasis and a careful glandular excision are common to minimize recurrence and achieve low complication rates [45]. Studies conducted on the effects of AAS use and abuse on the prostate gland have shown that the chronic use of these substances can promote prostatic hyperplasia and hypertrophy [42,46,47].…”
Section: The Association Of Aass With the Circulatory System And Sexu...mentioning
confidence: 99%
“…Prostatic hyperplasia is characterized by increase in the number of cells in the prostate, whereas hypertrophy refers to the increase in the size of cells in this endocrine environment. Furthermore, there is evidence that the prolonged use of AASs increases the risk of developing prostate cancer [42,46,47]. However, these authors also suggest that further studies are needed to corroborate this evidence.…”
Section: The Association Of Aass With the Circulatory System And Sexu...mentioning
confidence: 99%